Inactivation of Zygosaccharomyces Rouxii using power ultrasound at different temperatures, pH and water activity condintions - S. KIRIMLI; B. KUNDUHOGLU (Chiriotti Editori, 2016)
In this study, the effect of ultrasound treatments (20 kHz) combined with mild temperatures (thermo-sonication) on the inactivation of Z. rouxii was examined. Additionally, the effect of pH (4 and 7) and water activity (aw 0.99 and 0.94) of the sonication medium on yeast inactivation was determined. The D(40-55) values at a thermo-sonication amplitude of 80% were shorter than that obtained at 40%. Using thermo-sonication, particularly at a low aw, was associated with a significant synergistic effect for Z. rouxii inactivation (p<0.05). In most thermo-sonications at 50° and 55°C, the FDA requirement of a 5-log cycle reduction could be achieved (>5.7-log reductions in <0.2-0.2 min). Our findings show that sonication offers advantages in terms of reduced duration and temperature of pasteurization, without a reduction in structural and sensory quality particularly for fruit juices.